The Deteriorating Effect of Poor Parental Skills on Children's Education and Mental Health - Ma. Theresa G. Kaligid; John Michael Villagorda Sasan; Mary Aianne Villegas (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
Parenting style is a psychological construct that describes how parents raise their children. This article examines the several parenting techniques used by families. Parenting techniques are becoming increasingly important in modern society. This research demonstrates parents' various strategies when raising their children and the numerous issues with modern parenting. The core cause of most teenage mental health problems is found to be related to parenting style. Most parents employ a variety of parenting styles based on their culture and societal demands. It describes parenting styles and how they affect children's development. The impact of socioeconomic class on parenting style is also examined in the study. The results of this study are (1) parenting style can be thought of as an overall structure that represents the general emotional environment between the parent and the child; (2) Diverse civilizations have different parenting behaviours and influences; (3) Parent-child relationships allow children to develop physically, emotionally, and socially. The conclusion is that parenting patterns are very influential on the growth and development of children. Family parenting has an impact on the social and emotional development of children.